EXAMINING THE PROCESS OF DECOMPOSITION AND CARBON CYCLING IN ’FADAMA’ COASTAL WETLANDS: A CASE STUDY OF HEAPING WETLANDS ECOSYSTEM - Dasat Shwamyil, George; Danjuma, G.; Chundusu, E. S. (FUDMA JOURNAL OF SCIENCES, 2020)
Wetlands provide several ecosystem services including carbon capture and storage, water filtration, nutrient cycling, and support agriculture among others. The biogeochemical process and decomposition parameters in â€˜Fadama’ wetland soils comprising of Gada biyu, Pwomol and Kpang referred to as sites A, B, and C respectively all of Heipang District in Barkin Ladi, Plateau State was investigated using standard operating procedures (SOP). Results of investigations revealed that soils from Kpang had slightly higher water content (34.52%) than those from Pwomol (33.48%) and Gada biyu (32.03%). While soils from Gada biyu had the highest solid organic matter (SOM) (10.79%) followed by Pwomol (8.15%) as Kpang had the least (7.85%). Gada biyu soils had the lowest Phenol oxidases activity (1536.56 nmol dicq g-1 h-1) while those from Pwomol (5340.44 nmol dicq g-1 h-1) was highest. All sites had similar concentrations of soil phenolics (76.58 Âµg g-1, 79.98Âµg g-1, and 83.25Âµg g-1). The activity of hydrolyses (Î²-glucosidase) in Gada biyu soil (2.93 nmol g-1 min-1) was lower than those from Pwomol (6.13 nmol g-1 min-1). These parameters indicate the level of biogeochemical processes in the soil at each site. Gada biyu had the highest rate of CH4 (0.84 ug g-1h-1) flux. Decomposition of organic matter, carbon cycling and greenhouse gas storage in wetland soil, is due to the anoxic condition comprising of low oxygen availability, cool temperatures, anaerobic conditions, reduced microbial activity, and the quality of organic matter substrates in such soils. Anthropogenic disturbances affecting wetlands must be discouraged to promote vital ecosystem services.